Preparation and in-vitro Evaluation of Secnidazole as Periodontal In-situ Gel for Treatment of Periodontal Disease - Raheema, Dheyaa A; Kassab, Hanan Jalal (Iraqi Journal of Pharmaceutical Sciences, 2022)
This study aims to develop a thermosensitive mucoadhesive periodontal in situ gel of secnidazole for local release of drug for treatment of periodontitis, in order to increase the drug residence time and to increase patient compliance while lowering the side effects of the drug.Cold method was used to prepare 30 formulas of secnidazole periodontal in situ gel, using different concentrations of thermosensitive polymers (poloxamer407 alone or in combination with poloxamer 188) and methyl cellulose (MC ) or hydroxypropyl methylcellulose (HPMC K4M )in different concentrations used as mucoadhesive polymer and the resultant formulations were subjected to several tests such as   gelation temperature GT, appearance and pH value. The formulas with the most appropriate GT were subjected to in-vitro drug release. Three formulas were chosen with appropriate release, F6 (15% P407, 1% MC), F29 (18%P407,3% P188, 0.8% HPMC) and F30 (18%P407,3% P188, 1% HPMC). These formulas were subjected to mucoadhesive force, viscosity, drug content, spreadability, gelation time and Fourier Transform Infrared (FTIR) compatibility studies.The results indicates that formula F29 and F30 have best gelation temperatures (33°C, 32°C) gel strength (1.5h,2h) mucoadhesive force of (17.1, 23.4 dyne/cm2 ) and in-vitro drug release (98.2%, 100%) respectively during 3.5h and gelation, time about 10 seconds for both formulas and FTIR spectrum study show absence of important interaction between secnidazole and the polymers used.